Pengaruh Hambatan Cincin Terhadap Fenomena Flooding Dalam Aliran Dua Fase Berlawanan Arah Pipa Vertikal - Robbi, Nur; Wahyudi, Slamet; Widyanuriyawan, Denny (Rekayasa Mesin, 2013)
Two-phase flow is widely used in daily life and industry, such as the installation of sludge pumps that drain liquid and solid or on the installation of air condition that drain freon fluid in the gas and liquid phase. However, in the two-phase flow also did not rule out the occurrence of barriers, barriers occur because of the crust, reduction and enlargement of the pipe. Besides that the twophase flow is also very useful as a coolant in the pipeline contained hot phase therein. In a Variation of ring barriers Dp/Dc = 1,Dp/Dc=1,06,Dp/Dc=1,125 and Dp/Dc=1,2, the fluid is streamed from the top passing through the water injector, while the air from the compressor is streamed from the down through the air injector. Water pressure ranging from 3-6 L/min and the air was varied ranging from 3-10 L/s. The test results obtained the flooding phenomenon that occurs because of the pressure difference in the pipe that causes fluid that move from the top through the injector can not go down but it back upwards because of the air pressure is greater than the water. In the ring barriers Dp/Dc = 1,Dp/Dc=1,06,Dp/Dc=1,125 and Dp/Dc=1,2, the fastest flooding phenomenon occurs on the ring barriers Dp/Dc=1,2 in water debit 6 L/min, air 6 L/s, this is because the bigger barriers make the occurrence of the phenomenon of flooding be faster, flooding phenomenon is also due to pressure differences in the test tube, the bigger debit of air and water make the flooding phenomenon be faster.Keywords: The phenomenon of flooding, air and water discharge, pressure differences